The influence of detector size relative to field size in small-field photon-beam dosimetry using synthetic diamond crystals as sensors. (August 2015) - Ade, N.; Nam, T.L.
Abstract: The choice of a detector for small-field dosimetry remains a challenge due to the size/volume effect of detectors in small fields. Aimed at selecting a suitable crystal type and detector size for small-field dosimetry, this study investigates the relationship between detector and field size by analysing output factors (OFs) measured with a Diode E (reference detector), a Farmer chamber and synthetic diamond detectors of various types and sizes in the dosimetry of a 6 MV photon beam with small fields between 0.3×0.3 cm 2 and 10×10 cm 2 . The examined diamond sensors included two HPHT samples (HP1 and HP2) and six polycrystalline CVD specimens of optical grade (OG) and detector grade (DG) qualities with sizes between 0.3 and 1.0 cm. Each diamond was encapsulated in a tissue-equivalent probe housing which can hold crystals of various dimensions up to 1.0×1.0×0.1 cm 3 and has different exposure geometries ('edge-on' and 'flat-on') for impinging radiation. The HPHT samples were found to show an overall better performance compared to the CVD crystals with the 'edge-on' orientation being a preferred geometry for OF measurement especially for very small fields. For instance, down to a 0.4×0.4 cm 2 field a maximum deviation of 1.9% was observed between the OFs measured with Diode E and HP2 in the 'edge-on' orientation compared to a 4.6% deviation in the 'flat-on' geometry. It was observed that for fields below 4×4 cm 2, the dose deviation between the OFs measured with the detectors and Diode E increase with increasing detector size. It was estimated from an established relationship between the dose deviation and the ratio of detector size to field size for the detectors that the dose deviation probably due to the volume averaging effect would be >3% when the detector size is >3/4 of the field size. A sensitivity value of 223 nC Gy −1 mm −3 was determined in a 0.5×0.5 cm 2 field with HP2 compared to a value of 159.2 nC Gy −1 mm −3 obtained with the diode. The results of this study indicate that with careful selection of a suitable crystal type of a given size and orientation the relative dose measured with the diamond probe in small fields would agree favourably within ±2% with that measured with a small-field detector but with a higher sensitivity value. Highlights: Influence of detector size relative to field size in small fields was investigated. OFs obtained with various diamonds and Diode E for 6 MV photons were compared. A dose deviation within 3% was obtained for detector size <3/4 of field size. Selected diamond of a given size and orientation have OFs within ±2%. Compared to Diode E, the diamond probe displayed a higher sensitivity value.